(untitled) (Studia theodisca, 2023)
Through an analysis of Goethe’s essay «Von deutscher Baukunst» this study intends to highlight the programatic value of the same for the first authentically German cultural movement, i.e. the «Storm and Stress». The paradigmatic figure of Erwin von Steinbach, the ingenious architect of Strasbourg Cathedral, sympathetically overshadows that of the medieval architect Eudes de Montreuil, whose re-evaluation is due to André Thevet from a patriotic and idealized Renaissance point of view. This is a curious parallelism in the name of creative genius and it represents the starting point of an important process that was to lead to a German aesthetic and literary renewal intended to overcome foreign models, especially French, and also to a re-evaluation of Gothic architecture in a patriotic and nationalist key.